2009
DOI: 10.1113/jphysiol.2009.172916
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase phosphorylation in treadmill‐running mice: role of vascular signalling kinases

Abstract: The intracellular signalling kinases Akt/protein kinase B (Akt), protein kinase A (PKA) and adenosine monophosphate-activated protein kinase (AMPK) are phosphorylated in response to increased mechanical force or perfusion rate in cultured endothelial cells or isolated blood vessels. All three kinases phosphorylate endothelial nitric oxide synthase (eNOS) on serine (S) 1177, while Akt and PKA additionally phosphorylate eNOS on S617 and S635 respectively. Although these kinases might contribute to subsequent act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
115
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(121 citation statements)
references
References 55 publications
(108 reference statements)
5
115
0
Order By: Relevance
“…Previous studies showed inconsistent effects of exercise on eNOS expression in the vasculature. For example, several groups reported that both low and moderate exercise increased eNOS protein expression, whereas others indicated that exercise did not change the expression of eNOS in the vasculature (12,32,37,55). In addition, Bitar et al (5) showed that diabetes increased eNOS protein, whereas our previous study showed that diabetes status was not associated with a change in eNOS protein expression within the aorta (54).…”
Section: Discussionmentioning
confidence: 44%
“…Previous studies showed inconsistent effects of exercise on eNOS expression in the vasculature. For example, several groups reported that both low and moderate exercise increased eNOS protein expression, whereas others indicated that exercise did not change the expression of eNOS in the vasculature (12,32,37,55). In addition, Bitar et al (5) showed that diabetes increased eNOS protein, whereas our previous study showed that diabetes status was not associated with a change in eNOS protein expression within the aorta (54).…”
Section: Discussionmentioning
confidence: 44%
“…27,28,[39][40][41][42] eNOSderived NO has been known to have a pivotal role in the modulation of vascular tone and function. 6,7 Taken together, our results allow us to propose that, ROS/RNS excess in peripheral resistance vessels during I/R injury may blunt PI3K/Akt/eNOS pathway, thus triggering endothelial dysfunction. A schematic representation of the proposed mechanism is shown in Figure 10.…”
Section: Discussionmentioning
confidence: 86%
“…It should be noted that NO is the primary regulator of vascular function, because it induces vasodilatation, inhibits platelet adhesion and aggregation, and reduces leukocyte-endothelial cell interaction. [5][6][7] This could explain the critical role of NO in IPC-induced endothelial protection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that both acute and regular aerobic exercise in swimmers and sedentary group increase blood NOx levels. 23,47,48 The best-established stimulus of NO production is shear stress, which increases during increased blood flow and can increase NOS activity. Furthermore, it has been reported that all isoforms of NOS can be regulated by transcription with hypoxia.…”
Section: Discussionmentioning
confidence: 99%